2019
DOI: 10.3390/cancers11070921
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Temozolomide Resistant Primary GBM Stem-Like Cells and Recurrent GBM Identifies Up-Regulation of the Carbonic Anhydrase CA2 Gene as Resistance Factor

Abstract: About 95% of patients with Glioblastoma (GBM) show tumor relapse, leaving them with limited therapeutic options as recurrent tumors are most often resistant to the first line chemotherapy standard Temozolomide (TMZ). To identify molecular pathways involved in TMZ resistance, primary GBM Stem-like Cells (GSCs) were isolated, characterized, and selected for TMZ resistance in vitro. Subsequently, RNA sequencing analysis was performed and revealed a total of 49 differentially expressed genes (|log2-fold change| &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…CAXII inhibitors also reduced the growth of TMZ-resistant GSCs by inhibiting P-glycoprotein-mediated drug efflux 109 . TMZ resistance in GSCs was further shown to be CAII mediated, with the broader CA inhibitor acetazolamide showing efficacy in combination with TMZ in xenograft models 110 , 111 . Furthermore, CAIX is suggested as a target in GBM for CAR T-cells that could be effective against GSCs 112 .…”
Section: The Relationship Between Acidic Stress and Gscsmentioning
confidence: 98%
“…CAXII inhibitors also reduced the growth of TMZ-resistant GSCs by inhibiting P-glycoprotein-mediated drug efflux 109 . TMZ resistance in GSCs was further shown to be CAII mediated, with the broader CA inhibitor acetazolamide showing efficacy in combination with TMZ in xenograft models 110 , 111 . Furthermore, CAIX is suggested as a target in GBM for CAR T-cells that could be effective against GSCs 112 .…”
Section: The Relationship Between Acidic Stress and Gscsmentioning
confidence: 98%
“…Recently, Hannen and colleagues reported that CA II is upregulated in TMZ resistant stem-like cells compared to control cells [ 81 ]. The same phenomenon was observed in clinical specimens of first manifest and recurrent tumors.…”
Section: Use Of Ca Inhibitors In Brain Tumorsmentioning
confidence: 99%
“…PAD activation has indeed been linked to hypoxia in the CNS [53][54][55] and deiminated KEGG (Kyoto Encyclopedia of Genes and Genomes) protein pathways for HIF-1 regulation have been identified to be enriched in animal models of hypoxia-and cancer-resistance [56,57]. PADs also modulate neuronal stem cell growth and death [58], which is of importance considering that GBM tumour invasion, progression and chemo-resistance of recurrent GBM are partly linked to stem-ness [59,60]. Therefore, effects of PAD inhibitors on PAD mediated pathways including EV-mediated export of a range of cancer and hypoxia related microRNAs are also of considerable interest.…”
Section: Introductionmentioning
confidence: 99%